Mental Health Literacy of Youth That Have a Family Member With a Mental Illness: Outcomes From a New Program and Scale - Riebschleger, Joanne; Costello, Shane; Cavanaugh, Daniel L.; Grové, Christine (Frontiers in Psychiatry, 2019)
A program evaluation examined mental health literacy levels and coping outcomes for youth (ages 10-16), before and at the end of their participation in a manualized, school-based mental health literacy program called Youth Education and Support (YES). Most of the youth reportedly had a parent or other family member with a mental health disorder such as depression, anxiety, and/or substance abuse. The mental health literacy levels of program participants from pre to post were evaluated with the developing Knowledge of Mental Illness and Recovery (K-MIR) scale. This scale was validated using item-response theory, demonstrating good psychometric properties. Youth answered two coping questions about their use of positive coping during the program and coping skills compared from pre to post intervention. Findings revealed that youth levels of mental health literacy increased significantly from pre to post program participation. Over 90% of the youth reported an improved use of positive coping strategies from pre to post intervention. The program appeared to deliver enhanced levels of literacy and coping for this sample of youth. The scale appeared to be appropriate to measure youth mental health literacy. Recommendations for practice, policy, and research are offered.